Gibberellic Acid, Ozone and 1-Methylcyclopropene on the Gray Mold Control in 'Avant Garde' Rose - Favero, B. T. [UNESP]; Benato, E. A.; Dias, G. M.; Cia, P.; Castro, ACR; Cuquel, F. L.; Loges, V (Int Soc Horticultural Science, 2015)
Gray mold caused by Botrytis cinerea is considered the major disease of greenhouse grown flowers. The goal of this study was to evaluate the effects of gibberellic acid (GA(3)), ozone, and 1-MCP, applied on postharvest, on the gray mold control in 'Avant Garde' rose. Rose flowers were artificially inoculated with B. cinerea (10(4) conidia ml(-1)) and non-inoculated. After treatments, roses were stored under room conditions (20 +/- 2 degrees C/80 +/- 5% RH) and checked for gray mold incidence and severity. Spraying of GA(3) at 25, 50, and 75 mg L-1 on non-inoculated roses reduced the area under the disease progress curve (AUDPC) of gray mold incidence in 41, 40 and 54%, respectively. Continuous application of ozone at 2.7 ppm reduced 14-folds B. cinerea sporulation. On the other hand, 1-MCP did not control gray mould in rose. These results showed that GA(3) sprays and ozone contribute to postharvest control of gray mold in cut rose and can be utilized on integrated disease management.
Keywords: Rosa hybrida; Botrytis cinerea; postharvest; quality; alternative control